Availability, cost, and prescription patterns of antihypertensive medications in primary health care in China: a nationwide cross-sectional survey. Issue 10112 (9th December 2017) - Su, Meng; Zhang, Qiuli; Bai, Xueke; Wu, Chaoqun; Li, Yetong; Mossialos, Elias; Mensah, George A; Masoudi, Frederick A; Lu, Jiapeng; Li, Xi; Salas-Vega, Sebastian; Zhang, Anwen; et al.
Summary: Background: Around 200 million adults in China have hypertension, but few are treated or achieve adequate control of their blood pressure. Available and affordable medications are important for successfully controlling hypertension, but little is known about current patterns of access to, and use of, antihypertensive medications in Chinese primary health care. Methods: We used data from a nationwide cross-sectional survey (the China Patient-Centered Evaluative Assessment of Cardiac Events Million Persons Project primary health care survey), which was undertaken between November, 2016 and May, 2017, to assess the availability, cost, and prescription patterns of 62 antihypertensive medications at primary health-care sites across 31 Chinese provinces. We surveyed 203 community health centres, 401 community health stations, 284 township health centres, and 2474 village clinics to assess variation in availability, cost, and prescription by economic region and type of site. We also assessed the use of high-value medications, defined as guideline-recommended and low-cost. We also examined the association of medication cost with availability and prescription patterns. Findings: Our study sample included 3362 primary health-care sites and around 1 million people (613 638 people at 2758 rural sites and 478 393 people at 604 urban sites). Of the 3362 sites, 8·1% (95% CI 7·2–9·1) stocked no antihypertensive medications and 33·8% (32·2–35·4) stocked all four classes that were routinely used. Village clinics and sites in the western region of China had the lowest availability. Only 32·7% (32·2–33·3) of all sites stocked high-value medications, and few high-value medications were prescribed (11·2% [10·9–11·6] of all prescription records). High-cost medications were more likely to be prescribed than low-cost alternatives. Interpretation: China has marked deficiencies in the availability, cost, and prescription of antihypertensive medications. High-value medications are not preferentially used. Future efforts to reduce the burden of hypertension, particularly through the work of primary health-care providers, will need to improve access to, and use of, antihypertensive medications, paying particular attention to those with high value. Funding: CAMS Innovation Fund for Medical Science, the Entrusted Project from the China National Development and Reform Commission, and the Major Public Health Service Project from the Ministry of Finance of China and National Health and Family Planning Commission of China.